2014
DOI: 10.1016/s1470-2045(14)70266-9
|View full text |Cite
|
Sign up to set email alerts
|

The biological and clinical effects of smoking by patients with cancer and strategies to implement evidence-based tobacco cessation support

Abstract: Tobacco use is an established risk factor for the development of several cancers; however, far less work has been done to understand the effects of continued smoking on cancer treatment outcomes, and structured tobacco cessation efforts are not well incorporated into the standard care for patients with cancer. In this Review we discuss the known biological effects of smoking on cancer cell biology and emphasise the clinical effects of continued smoking in patients with cancer treated with chemotherapy or radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 82 publications
2
107
0
1
Order By: Relevance
“…10,23 Continued smoking among cancer patients also stimulates proliferation and tumorigenesis and reduces apoptosis in cancer cells. 50 Exposures of cancer cells to smoking also increase multidrug resistance, which then increase the risks for cancer recurrence and decrease response to treatment. 50 Moreover, continuing smokers tend to develop more late-stage complications, such as impaired wound healing, vascular injury, or a direct irritant, 10,29 which may contribute to poor mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,23 Continued smoking among cancer patients also stimulates proliferation and tumorigenesis and reduces apoptosis in cancer cells. 50 Exposures of cancer cells to smoking also increase multidrug resistance, which then increase the risks for cancer recurrence and decrease response to treatment. 50 Moreover, continuing smokers tend to develop more late-stage complications, such as impaired wound healing, vascular injury, or a direct irritant, 10,29 which may contribute to poor mortality.…”
Section: Discussionmentioning
confidence: 99%
“…50 Exposures of cancer cells to smoking also increase multidrug resistance, which then increase the risks for cancer recurrence and decrease response to treatment. 50 Moreover, continuing smokers tend to develop more late-stage complications, such as impaired wound healing, vascular injury, or a direct irritant, 10,29 which may contribute to poor mortality. Smokers tend to simultaneously engage in other risky health behaviors, such as substance abuse, problem drinking, physical inactivity, not adhering to medication regimens, and missing treatment days, 10,51 which may lead to worse mortality outcomes, although this study controlled for some of these risky behaviors, including problem drinking and nutritional status (BMI).…”
Section: Discussionmentioning
confidence: 99%
“…The process of metastasis may be classically divided into a number of steps: Invasion of tumor cells into the surrounding tissues, penetration of vessels and migration toward distant sites of the body away from the primary sites (74). At present, several clinical studies in humans revealed an association between smoking and an increase in the metastasis of lung cancer (75)(76)(77)(78). The α7nAChR is expressed in SCLC and NSCLC cells (24).…”
Section: Function and Mechanisms Of α7nachr On Metastasismentioning
confidence: 99%
“…Evidence has shown that continued smoking by cancer patients leads to adverse cancer treatment outcomes and affects survival [4][5][6] . Smoking diminishes treatment effectiveness, particularly for radiation therapy and chemotherapy; it also exacerbates side effects, interferes with wound healing, and can be a risk factor for a wide range of pulmonary, cardiovascular, infectious, and woundrelated complications 3,4,[7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Smoking diminishes treatment effectiveness, particularly for radiation therapy and chemotherapy; it also exacerbates side effects, interferes with wound healing, and can be a risk factor for a wide range of pulmonary, cardiovascular, infectious, and woundrelated complications 3,4,[7][8][9] . Patients who smoke also have a higher risk of developing a second primary cancer or experiencing a cancer recurrence.…”
Section: Introductionmentioning
confidence: 99%